Calcium imaging of muscle cells treated with snake myotoxins reveals toxin synergism and presence of acceptors - Cintra Francischinelli, Mariana (2009)
Snake myotoxins have a great impact on human health worldwide. Most of them adopt a phospholipase A2 fold and occur in two forms which often co-exist in the same venom: the Asp49 toxins hydrolyse phospholipids, whilst Lys49 toxins are enzymatically inactive. To gain insights into their mechanism of action, muscle cells were exposed to Bothrops myotoxins, and cytosolic Ca2+ and cytotoxicity were measured. In both myoblasts and myotubes, the myotoxins induced a rapid and transient rise in cytosolic [Ca2+], derived from intracellular stores, followed, only in myotubes, by a large Ca2+ influx and extensive cell death. Myoblast viability was unaffected. Notably, in myotubes Asp49 and Lys49 myotoxins acted synergistically to increase the plasma membrane Ca2+ permeability, inducing cell death. Therefore, these myotoxins may bind to acceptor(s) coupled to intracellular Ca2+ mobilization in both myoblasts and myotubes. However, in myotubes only, the toxins alter plasma membrane permeability, leading to death.